Comparison of Modulation of Kv1.3 Channel by Two Receptor Tyrosine Kinases in Olfactory Bulb Neurons of Rodents - Colley, B. (2004)
Activation of the receptor tyrosine kinase (RTK), insulin (IRK), or neurotrophin B (TrkB) was characterized and compared in olfactory bulb neuron (OBN) cultures from Sprague Dawley rats and sv129 B6 mice. Current suppression attributed to modulation of the delayed rectifier, Kv1.3, a voltage-gated potassium (Kv) channel of the Shaker family, was observed following acute application of the growth factors, insulin, or brain-derived neurotrophic factor (BDNF), to mitral cells of either rodent model. Using site-directed mutagenesis of putative tyrosine phosphorylation recognition motifs in the channel, we find that stimulation of Kv1.3 with these growth factors causes multiple phosphorylation, albeit via different residue combinations that are RTK specific.